ONLINE RELIGION AND RETHINKING THE DA’WAH AUTHORITY TOWARD AN INCLUSIVE DA’WAH: A CONCEPTUAL STUDY - Adeni, Adeni - (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2020)
This paper aims to examine the concept of da’wah authority in the context of the relationship between religion and new media. The presence of new media has an impact on the development of Islamic da'wah especially regarding the issue of da'wah authority. By using a qualitative method based on library research, this paper concludes that first, the da’wah authority has shifted from the sender authority to the recipient authority, who is free and active in interpreting da'wah messages. Second, in the realm of new media, there is no clear boundary between the sender and da’wah messages recipient so that someone can be both the sender and the recipient of da'wah at the same time. Third, new media allows the opening of space for dialogue between religions. Fourth, feedback from da'wah recipients requires that the message conveyed must be valid, argumentative, and convincing. Fifth, da'wah in new media can no longer be forced to be accepted by the recipient except based on certain considerations from the recipient.Makalah ini bertujuan mengkaji konsep otoritas dakwah dalam konteks hubungan antara agama dan media baru (new media). kehadiran media baru berdampak pada perkembangan dakwah Islam khususnya terkait dengan otoritas dakwah. Dengan menggunakan metode kualitatif berdasarkan studi pustaka (library research), makalah ini menyimpulkan bahwa pertama, otoritas dakwah telah bergeser dari otoritas pengirim menjadi otoritas penerima yang bebas dan aktif dalam menafsirkan pesan dakwah. Kedua, dalam ranah new media tidak ada batasan yang jelas antara pengirim dan penerima pesan dakwah sehingga seseorang dapat menjadi pengirim sekaligus penerima dakwah. Ketiga, media baru memungkinkan terbukanya ruang dialog antar agama. Keempat, umpan balik dari penerima dakwah mengharuskan pesan yang disampaikan harus valid, argumentatif, dan meyakinkan. Kelima, dakwah di media baru tidak bisa lagi dipaksa untuk diterima oleh penerima kecuali berdasarkan pertimbangan tertentu dari penerima.